Journal of Cardiology and Vascular Medicine 2019
DOI: 10.17303/jcvm.2017.3.102
|View full text |Cite
|
Sign up to set email alerts
|

Mr-Proanp Rises during Exercise Even after Surgical Closure of the Left Atrial Appendage: A Sub-Study of the Laacs Randomized Study

Abstract: Methods: A group of 19 patients who had undergone elective open heart surgery, and who had been randomized to either the LAA-closure group (n=9), or to the LAA-open group (n=10) performed a standard bicycle exercise test, at least six weeks after the operation. Closure of the LAA was confirmed by Transesophageal Echocardiography (TEE). Venous blood samples were collected before the test, and within the first two minutes of recovery after maximum work-load. Conclusion: This study shows that plasma MR-proANP inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…A randomized trial of 187 patients also found a lower risk of strokewith LAAO but did not find a difference in mortality, perhaps because of the small sample size. 28 The ongoing Left Atrial Appendage Occlusion Study III trial (NCT01561651) plans to enroll 4700 patients, but that trial was limited to high-risk patients with documented AF or atrial flutter undergoing CABG and will not address the population without AF or those undergoing valve surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial of 187 patients also found a lower risk of strokewith LAAO but did not find a difference in mortality, perhaps because of the small sample size. 28 The ongoing Left Atrial Appendage Occlusion Study III trial (NCT01561651) plans to enroll 4700 patients, but that trial was limited to high-risk patients with documented AF or atrial flutter undergoing CABG and will not address the population without AF or those undergoing valve surgery.…”
Section: Discussionmentioning
confidence: 99%